Impact of oral anticoagulation choice on healthcare utilization for the primary treatment of venous thromboembolism. (December 2020) - Lutsey, Pamela L; MacLehose, Richard F; Claxton, J'Neka S; Walker, Rob F; Adam, Terrence J; Alonso, Alvaro; Zakai, Neil A
Little is known about the impact of oral anticoagulation (OAC) choice on healthcare encounters during venous thromboembolism (VTE) primary treatment. Among anticoagulant-naïve patients with VTE, we tested the hypotheses that healthcare utilization would be lower among users of direct OACs (DOACs; rivaroxaban or apixaban) than among users of warfarin. MarketScan databases for years 2016 and 2017 were used; healthcare utilization was identified in the first 6 months after initial VTE diagnoses. The 23, 864 patients with VTE had on average 0.2 ± 0.5 hospitalizations, spent 1.3 ± 5.2 days in the hospital, had 5.7 ± 5.1 outpatient encounters, and visited an emergency department 0.4 ± 1.1 times. As compared to warfarin, rivaroxaban and apixaban were associated with fewer hospitalizations, days hospitalized, outpatient office visits, and emergency department visits after accounting for age, sex, comorbidities, and medications. Hospitalization rates were 24% lower (incidence rate ratio (IRR): 0.76; 95% CI: 0.69, 0.83) with rivaroxaban and 22% lower (IRR: 0.78; 95% CI: 0.71, 0.87) with apixaban, as compared to warfarin (IRR: 1.00 (reference)). Healthcare utilization was similar between apixaban and rivaroxaban users. Patients with VTE prescribed rivaroxaban and apixaban had lower healthcare utilization than those prescribed warfarin, while there was no difference when comparing apixaban to rivaroxaban. These findings complement existing literature supporting the use of DOACs over warfarin.